2013
DOI: 10.1108/17542411311303239
|View full text |Cite
|
Sign up to set email alerts
|

Gender diversity in the boards of directors of Brazilian businesses

Abstract: PurposeThis study aims to analyse the gender composition of the 99 most liquid Brazilian companies listed in the Brazilian stock exchange (BM&FBovespa) in 2011. It proposes a discussion about gender inequality in Brazilian companies and provides data, made available for the first time to national and international literature, on gender composition in Brazilian boards.Design/methodology/approachThis is a quantitative study, whose data were collected from the Annual Report of Corporate Governance of Listed Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 30 publications
3
51
0
18
Order By: Relevance
“…Overall, it appears that there has been little progress toward integrating a diversity mindset into Brazilian organizational culture (e.g. Irigaray and Vergara, 2011;Jabbour et al, 2011;Lazzaretti et al, 2013;Santos et al, 2008;Saraiva and Irigaray, 2009;Vasconcelos, 2012Vasconcelos, , 2015 since the pioneer investigations conducted by Fleury (1999Fleury ( , 2000. Despite the limits of this study, the case units sample showed to have huge difficulties to mitigate organizational age bias effects in their headcount.…”
Section: Discussionmentioning
confidence: 75%
“…Overall, it appears that there has been little progress toward integrating a diversity mindset into Brazilian organizational culture (e.g. Irigaray and Vergara, 2011;Jabbour et al, 2011;Lazzaretti et al, 2013;Santos et al, 2008;Saraiva and Irigaray, 2009;Vasconcelos, 2012Vasconcelos, , 2015 since the pioneer investigations conducted by Fleury (1999Fleury ( , 2000. Despite the limits of this study, the case units sample showed to have huge difficulties to mitigate organizational age bias effects in their headcount.…”
Section: Discussionmentioning
confidence: 75%
“…First, this study looks into the role of gender diversity on various performance metrics, answering the call made by Adams and Ferreira (2009) and Kiliç and Kuzey (2016) for more research on the effects of women representation in top management in relatively unexplored settings. Also, our study complements the emerging body of work focused on the effects of gender diversity on performance in developing economies (e.g., Lazzaretti et al, 2013;Liu et al, 2014;Kiliç and Kuzey, 2016).…”
Section: Introductionmentioning
confidence: 73%
“…The board of directors is the most important organ of the company who are responsible for the management of the company and the directors decide the strategy for the business operation (Aina, 2013). The board is also the most important internal control mechanism in corporate governance which is used to curb agency issues in the corporation (Lazzaretti, Godoi, Camilo, & Marcon, 2013). Nevertheless, the impact of diversity on earnings management is unknown in developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%